Influence of the Initial Carbon/Nitrogen Ratio of the Substrate on the Production of Biomethane in a Continuous Reactor - FAGBEMI, LATIF ADENIYI; SAFIOU, BOURAIMA; ADAMON, DAVID G F; EKOUEDJEN, EVRARD KAROL (My University, 2020)
The prediction of biogas production is based on different mathematical models of anaerobic digestion. Several models exist and make it possible to describe the anaerobic processes with a reduced number of parameters but especially with various methods of resolution, thus posing the problem of the precision of the results obtained. The present model is based on the AM2HN (Anaerobic Model N°2 Hydrolyse Nitrogen) model and predicts biomethane production from the initial C/N (Carbon/Nitrogen) ratio of the substrate. This model has been implemented in Scilab computational software through a classical Runge Kutta numerical resolution method of order 4. The model is then validated by performing a comparative study between the results from the model and those from the literature under the same conditions. Simulations and comparisons with the results from the scientific literature show that the numerical results are satisfactory with respect to the experimental data. In addition, the cumulative volume of simulated biomethane decreases slightly as the C/N ratio increases in a range of 10/1 to 14/1. On the other hand, for a C/N ratio ranging from 16/1 to 22/1, this volume increases progressively and peaks at 22/1. However, the cumulative volume decreases slightly as the C/N ratio increases beyond this optimal value. In agreement with the results of the literature, it appears from the present study that the optimal C/N ratio depends on the type of substrate to be treated and in the case of solid substrates, it is between 20/1 and 25/1.
Keywords: Methanation; Biogas; modelling; Carbon/; nitrogen; methane